SIMULATION OF THE RECIPE COMPOSITION OF SAUCES FOR HEALTH PURPOSES BASED ON THE FUNCTIONAL COMPOSITIONS OF DIETARY SUPPLEMENTS - ANTONENKO АRTEM; BAL-PRYLYPKO, LARYSA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article provides the scientific basis and development of a methodology for creating functional sauce recipes based on functional compositions. This process is founded on the principle of food combinatorics, which ensures a well-reasoned selection of quantitative ratios between the main raw materials and food additives. This allows for the formation of the necessary organoleptic and physicochemical indicators, as well as achieving the required levels of nutritional and biological value. Modeling functional products involves creating a unified system whose parameters cannot be considered in isolation. Scientific approaches to modeling functional compositional mixtures and products utilizing them are aimed at optimizing the selection and ratio of ingredients, which ensures the achievement of a composition maximally compatible with nutritional value requirements and medico-biological standards. Considering the aforementioned aspects, the modeling results provide effective optimization of the product composition and its manufacturing process parameters. After the completion of multi-level experimental modeling, the functional components and product manufacturing technologies undergo testing in laboratory and industrial conditions, and are then adjusted. At the final stage, a comprehensive analysis of the key quality indicators of finished products is conducted, economic indicators are calculated, the technology is improved directly in production, regulatory documentation is prepared and approved, and industrial implementation is established. The application of this methodology for developing model functional compositions and food products contributes to increasing the efficiency of raw material utilization and expanding the assortment of products with a defined composition and health-promoting properties.